Red Ginger oleoresin nanoemulsion characteristics by ultrasonication - Nurma Pratiwi; Chandra Utami Wirawati; Dwi Eva Nirmagustina (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Red ginger is a biopharmaceutical plant that is used as herbal medicine. The use of red ginger in the food industry is mainly in an emulsion form, but that is unstable and hydrophobic. The ultrasonication technique could change the emulsion into a nanoemulsion to minimize these disadvantages. This research aimed to determine the effect of ultrasonication on red ginger oleoresin nanoemulsion characteristics. The study used a completely randomized design of 4 treatments based on sonication time (0, 30, 60, and 90 minutes). The study was analyzed by ANOVA Tukey's test at P ≤ 0.05, it showed that ultrasonication affected the characteristics of red ginger oleoresin nanoemulsion. The best result shows that in 90 minutes mixed time with transparent yellow colour. It is soluble in acetone, methanol, ethanol, and aquadest solvents. The best particle size is 572.43±8.72 nm, and antioxidant activity is (IC50) 16.34 ±1.33 ppm.©2022 JNSMR UIN Walisongo. All rights reserved.